Dental implants‐associated release of titanium particles: A systematic review. Issue 11 (2nd October 2018) - Suárez‐López del Amo, Fernando; Garaicoa‐Pazmiño, Carlos; Fretwurst, Tobias; Castilho, Rogerio M.; Squarize, Cristiane H.
Abstract: Objectives: The presence of titanium (Ti) particles around dental implants has been reported in the literature for decades. The prospective presence of Ti debris on soft tissues surrounding dental implants has not been systematically investigated and remains to be explored. Hence, this review aimed to evaluate the origin, presence, characteristics, and location of Ti particles in relation to dental implants. Material and methods: Literature searches were conducted by two reviewers independently based on the PRISMA guidelines. The systematic review identified studies on Ti particles derived from dental implants. We evaluated several parameters, including anatomical location, and the suspected methods of Ti particles release. Results: The search resulted in 141 articles, of which 26 were eligible and included in the systematic review of the literature. The investigations reported Ti and metal‐like particles in the soft (i.e., epithelial cells, connective tissue, and inflammatory cells) and hard (bone crest and bone marrow) tissues around the dental implants. Shape and size of the particles varied. The current literature reported a size range from 100 nm to 54 µm identified by multiple particles identification methods. Conclusion: Ti particles surrounding peri‐implant tissues are a common finding. Peri‐implantitis sites presented a higher number of particles compared to healthy implants. The particles were mostly around the implants and inside epithelial cells, connective tissue, macrophages, and bone. Various mechanisms were described as causes of Ti release, including friction during implant insertion, corrosion of the implant surface, friction at the implant–abutment interface, implantoplasty, and several methods used for implant surface detoxification.